Effects of invasive Pacific red lionfish Pterois volitans versus a native predator on Bahamian coral-reef fish communities - Albins, Mark A. (Biological invasions, 2013)
The recent irruption of Pacific red lionfish ( Pterois volitans ) on Caribbean and Atlantic coral reefs could prove to be one of the most damaging marine invasions to date. Invasive lionfish are reaching densities much higher than those reported from their native range, and they have a strong negative effect on the recruitment and abundance of a broad diversity of native coral-reef fishes. Otherwise, little is known about how lionfish affect native coral-reef communities, especially compared to ecologically similar native predators. A controlled field experiment conducted on small patch-reefs in the Bahamas over an 8-week-period demonstrated that (1) lionfish caused a reduction in the abundance of small native coral-reef fishes that was 2.5 ± 0.5 times (mean ± SEM) greater than that caused by a similarly sized native piscivore, the coney grouper Cephalopholis fulva (93.7 vs. 36.3 % reduction); (2) lionfish caused a reduction in the species richness of small coral-reef fishes (loss of 4.6 ± 1.6 species), whereas the native piscivore did not have a significant effect on prey richness; (3) the greatest effects on the reef-fish community, in terms of both abundance and richness, occurred when both native and invasive predators were present; and (4) lionfish grew significantly faster (>6 times) than the native predator under the same field conditions. These results suggest that invasive lionfish have stronger ecological effects than similarly sized native piscivores, and may pose a substantial threat to native coral-reef fish communities.